2021
DOI: 10.1080/19932820.2021.1930346
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutrients and Mediterranean diet on the occurrence of gestational diabetes

Abstract: Background:The Mediterranean diet (MedDiet) is a dietary pattern effective in terms of prevention of many diseases such as gestational diabetes mellitus (GDM). Recently, many studies have paid attention to nutritional factors during pregnancy as a modifiable contributor to GDM risk. Objective: to investigate associations of nutrients intakes and MedDiet pattern of eating with risk of GDM. Subjects/Methods: This study conducted on N = 120; Pregnant women with GDM (n = 60) and without controls (n = 60). The diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…In this context, the Mediterranean diet (MD) might be beneficial for materno-foetal health (Biagi et al, 2019). For the mother, achieving a healthier dietary pattern, such as the MD, seems to lower the risk for gestational diabetes (Izadi et al, 2016;Mahjoub et al, 2021), gestational hypertension (Schoenaker et al, 2015) and is associated with lower triglycerides (Martin et al, 2016) and fasting blood glucose (Mahjoub et al, 2021) concentrations. As for the foetus, greater maternal MD adherence has been associated with a reduced occurrence of preterm birth, better lipoprotein concentration, and insulin sensitivity measured in the umbilical cord (Biagi et al, 2019;Gesteiro et al, 2012Gesteiro et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Mediterranean diet (MD) might be beneficial for materno-foetal health (Biagi et al, 2019). For the mother, achieving a healthier dietary pattern, such as the MD, seems to lower the risk for gestational diabetes (Izadi et al, 2016;Mahjoub et al, 2021), gestational hypertension (Schoenaker et al, 2015) and is associated with lower triglycerides (Martin et al, 2016) and fasting blood glucose (Mahjoub et al, 2021) concentrations. As for the foetus, greater maternal MD adherence has been associated with a reduced occurrence of preterm birth, better lipoprotein concentration, and insulin sensitivity measured in the umbilical cord (Biagi et al, 2019;Gesteiro et al, 2012Gesteiro et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, after summing the scores of the individual components, the overall score of the Mediterranean diet pattern ranged from 0 to 8. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Finally, after summing the scores of the individual components, the overall score of the Mediterranean diet pattern ranged from 0 to 8. 19 The Mediterranean diet is based on 8 items: vegetables, legumes, fruits and nuts, dairy products, cereals, red meat and its products, fish, the ratio of unsaturated fatty acids with a double bond to saturated fatty acids. The median intakes of these foods were calculated for each sex.…”
Section: Calculation Of Modified Mediterranean Diet Scorementioning
confidence: 99%
“…A recent meta-analysis of the randomized controlled trial showed the efficacy of MedDiet in preventing GDM [ 43 ]. A recent review examined the role of MedDiet in modulating immune response and inflammation during COVID-19 and showed that MedDiet reduced interleukin-6 and inflammatory markers [ 44 ]. A recent case–control study showed that MedDiet reduced GDM incidence [ 45 ], interestingly, women who have rs7903146 T-allele showed a high reduction of GDM compared to their counterparts who are not indicating a gene-diet interaction [ 46 ].…”
Section: Special Types Of Dietsmentioning
confidence: 99%